2020
DOI: 10.3390/sym12111813
|View full text |Cite
|
Sign up to set email alerts
|

Multiquadrics without the Shape Parameter for Solving Partial Differential Equations

Abstract: In this article, we present multiquadric radial basis functions (RBFs), including multiquadric (MQ) and inverse multiquadric (IMQ) functions, without the shape parameter for solving partial differential equations using the fictitious source collocation scheme. Different from the conventional collocation method that assigns the RBF at each center point coinciding with an interior point, we separated the center points from the interior points, in which the center points were regarded as the fictitious sources co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…To compare the proposed PRBF with the conventional PRBF, we firstly consider a steady-state groundwater flow problem [33]:…”
Section: Convergence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To compare the proposed PRBF with the conventional PRBF, we firstly consider a steady-state groundwater flow problem [33]:…”
Section: Convergence Analysismentioning
confidence: 99%
“…The fictitious sources were placed on the external domain by utilizing (25). The fictitious source boundaries were defined as [33,34] ∂Ω s = (x s j , y s j ) x s j = ηρ s j cos θ s j , y s j = ηρ s j sin θ s j (25) where ∂Ω s denotes the boundaries of fictitious sources. Figure 3 illustrates the MAE values of the conventional and proposed PRBFs with different orders (values of k).…”
Section: Convergence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Frank [10] compared the scattered data interpolation algorithms and pointed out that the MQ-RBF has a better fitting result. It can be used to solve partial differential equations [33] and has been widely used in geologic modeling [6]. It has also been adopted in our previous works [17][18][19].…”
Section: Rbf Functions and Shape Parametersmentioning
confidence: 99%
“…(asymmetric) data, whereas multiquadric equations are used to interpolate qualitative variables(Tsidaev, 2016;Yamamoto et al, 2018).Recent studies have shown the wide application and advantages of spatial interpolation methods using the Natural Neighbor (NN) interpolator and multiquadric equations(Belinha et al, 2017;Ku et al, 2020). The spatial interpolation methods NN and the radial basis function, also known as the study of multiquadric equations, allow the knowledge of the spatial behavior of variables at non-sampled locations, facilitating the decisionmaking(Sampedro et al, 2019;Millan et al, 2020).…”
mentioning
confidence: 99%